Muslim Women: Life and Role as Social Activists in the Southern Border Provinces - Abru ์Nurulhuda; Srisuk, Wanpichit (Journal of Social Sciences and Humanities Research in Asia, 2022)
The objectives of this research were; 1) to study ways of life and the social status of Muslim wornen social activists in the three southern border provinces, 2) to study roles of Muslim women as being social activists in the 3 southern border provinces, and, 3) to propose development guidelines for Muslim wornen to be able to play a role as social activist for social development in the 3 southern border provinces. This research was qualitative research. Data were collected by in-depth interviews with Muslim womnen social activists in Pattani, Yala, and Narathiwat as key informants-5 people per area, a total of 15 people, of which those affected by the unrest working to aid others affected. Content analysis was used, and it had shown that most Muslim woren had been active in advocating, mentoring, and helping female victims of domestic violences in which their roles and work processes included helping the victims making petition, on-site assistance for one-on-one advice, accomnmodating by coordinating with relevant organizations, and, among all important roles, calling for gender equality. Common issues found during work were the imbalance of work and famnily care times as a Muslim womnan and not being accepted by people with ingrained beliefs and attitudes in the fact that Muslim women come out as social activists were against Islamic belief. Besides, the victimns having a lack of trust in the social movement network’s activists whom tried to reach and help caused our work to be inefficient as it should had been. Based on the findings, it is possible to propose development guidelines for the Muslim women to play a role in social activism with 3 keystones that; relevant organizations must build knowledge and understanding towards social mobilization and try to build knowledge and better attitudes towards self-appreciation for Muslim women; network workflows need to be allocated to align more with Muslim women’s ways of lives; and, there should be more approaches and concepts of self-worth being passed on in the society.